Direito humano à educação: as infâncias do campo nos territórios da cidadania - Oliveira , Fernanda Alves de (2016)
This work entails an academic reflection on the right to education, and education as one of human rights. It presents the results of research on the actions for education / field in public policy, with the cutout in the Territories of Citizenship Program. The fact develop research in a Graduate Interdisciplinary Program in Human Rights, enabled discussions with different areas and fields of knowledge, including the field of law, Education, Geography, Public Policy and own field of Human Rights which is increasingly gaining spaces of academic discussions. Use of document analysis methodology, to answer the questions, "actions for childhood education developed by the Citizenship Territories Program, include the specificity of / in the field Education, articulating as a realization of the Human Right to Education" as "which conceptual ideas and referring to the model of development policies, citizenship, education in / Field and territorial approach present in the Territories of Citizenship program?". To trace a path to the responses of research problems, delimit the goals as each question, including propose to analyze the actions of the Citizenship Territories Program, related to education, with the intent to understand what the convergences and divergences with the Education conceptions of /in the field. The Rural Education, as well as the Citizenship Territories Program's objectives and the preparation of development projects "for the field," however, we question the service who are being defined such development projects in the service of agribusiness through the capitalist side, economic and urbanocêntrica, or the service of farmers, respecting their specificities, culture and decent living conditions. The research is justified by understanding the need to study the rights of children in the field of education, since there are laws that guarantee education for all, but we find in reality children with such rights denied or violated, including those they live their childhoods in the field.